A Comparative Study of Software Metrics for Analysis and Its Impact on Predictability - Yamini, G; Ganapathy, Gopinath (International Journal of Computer Sciences and Engineering, 2019)
Quality assurance is one of the important non-functional software requirements which many software products fail to satisfy. Current software market is driven mostly by urgency and competition. One of the methods to ensure software quality is a metrics-based approach. Software metrics have been used to quantitatively evaluate software products. Software metrics play an important role in developing high quality software as well as to improve the developer’s productivity. Metrics can help quantify previous work in a way that can directly guide future efforts. For example, projects of different sizes can require vastly different levels of effort, organizational structure, and management discipline. There is an increasing need for metrics adapted to the Object-Oriented (OO) paradigm to help manage and foster quality in software development. Object-oriented design patterns are an emergent technology: they are reusable micro-architectures, high level building blocks. A major benefit of object-oriented software development is the support for reuse provided by object-oriented and object-based languages. The usefulness of metrics is reviewed. The reliability is one of the most important attributes of software quality. The presumed objective of the estimation of the reliability consists in the analysis of the risk and of the reliability of the software-based systems. This paper presents the study of different suite in object-oriented (OO) design metric.